2021
DOI: 10.1108/cfri-09-2021-0187
|View full text |Cite
|
Sign up to set email alerts
|

Cryptocurrency as a safe haven for investment portfolios amid COVID-19 panic cases of Bitcoin, Ethereum and Litecoin

Abstract: PurposeThis article examines the susceptibility of cryptocurrencies to coronavirus disease 2019 (COVID-19) induced panic in comparison with major stock indices.Design/methodology/approachThe author employs the Bayesian structural vector autoregression to examine the phenomenon in Bitcoin, Ethereum and Litecoin from 2nd January 2020 to 30th June 2021. A similar analysis is conducted for major stock indices, namely S&P 500, FTSE 100 and SSE Composite for comparison purposes.FindingsThe results suggest that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 46 publications
2
13
0
1
Order By: Relevance
“…Goodell in 2021 [8,11]. COVID-19 has a positive impact on electronic cryptocurrencies in the later stages and drives the price of bitcoin up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Goodell in 2021 [8,11]. COVID-19 has a positive impact on electronic cryptocurrencies in the later stages and drives the price of bitcoin up.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the effect of COVID-19 on cryptocurrency in China and overseas is differentthe correlation between China and the price index of the digital currency is negative but it is positive overseas. Further research compares the economic phenomenon in cryptocurrencies with those in major stock indices and finds that cryptocurrencies are more vulnerable during the COVID-19 period [8]. The theory presented by Muhammad Abubakr Naeem in 2020, uses the asymmetric multifractal detrended fluctuation analysis (MF-DFA) to test the asymmetric efficiency of four specific cryptocurrencies -Bitcoin, Ethereum, Litecoin, and Ripple [9].…”
Section: Introductionmentioning
confidence: 99%
“…Hou et al ( 2021 ) also found a short-term negative effect of COVID-19 on Bitcoin prices but a long-term beneficial effect due to its features, such as digital payments, unbanked assets, and safer virus propagation. Marobhe ( 2022 ) proved that Bitcoin, Ethereum, and Litecoin all experienced sizable negative return shocks during the first wave of COVID-19; however, they bounced back in April 2020 and remained resilient to subsequent COVID-19 panic shocks.…”
Section: Prior Literaturementioning
confidence: 99%
“…Umar and Gubareva ( 2020 ) covered only Coronavirus Panic Index but explored Bloomberg Galaxy Crypto Index. Marobhe ( 2022 ) covered the corona Panic Index and demonstrated the longstanding resistance of cryptocurrencies to COVID-19. As such, previous studies used only one indicator to assess media exposure, frequently overlooking the different influences of various types of news reports, such as disinformation and public anger (Zhang et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Stock markets across the globe have experienced increasing volatility and significant negative returns since the outbreak of COVID-19 (Zhao et al , 2022; Uddin et al , 2021; Ashraf, 2020; Zhang et al , 2020; Baek et al , 2020; Marobhe, 2022). Some major stock indices such as Dow Jones Industrial Average, Nikkei, FTSE 100 and Shanghai Composite index have exhibited a downward trend with average drops ranging between 24 and 33% from late December 2019 to late March 2020 (Hui and Chan, 2022).…”
Section: Introductionmentioning
confidence: 99%